The Status and Guidelines of Reason in Light of the Quran and Sunnah: An Analytical Study - Mekki, Klaina; Putra, D.I. Ansusa (Asian Journal of Islamic Studies and Da'wah, 2025)
This study examines the status of reason in Islam through the Quran and Sunnah, highlighting its pivotal contribution to development of knowledge, scientific progress, and innovation. The research aims to emphasize the esteemed status of reason in Islam while outlining its proper boundaries to avoid its misuse in matters beyond its scope, such as the unseen and miracles. It also seeks to clarify the levels of reasoning and their distinctions to prevent individuals from falling victim to superstition or blind imitation. The study addresses the misconception propagated by Islam's detractors, who claim that the faith does not value intellect, posing questions about the extent to which reason can be employed, the necessary conditions for its use, and whether there is harmony or conflict between reason and revelation. The research employs an analytical methodology, examining the Quran and Sunnah to demonstrate the role and regulations of reason in Islam. Findings reveal that Islam elevates reason, defining its fields of application and encouraging its use to explore universal laws for the purpose of civilizational development and collective advancement of knowledge and human dignity. Furthermore, the study confirms that Islam promotes critical thinking to enhance societal thought, with the history of Muslim contributions to knowledge contradicting the distorted image spread by adversaries. It asserts that Muslims were once global leaders in intellectual and scientific domains.